Inflation's Domino Effect: Gas like and its effect on jeepney drivers and its commuters in the City of Manila - Cao, James Michael; Casalhay, Desiree Mae; Co, Angela Concesca; Dac-Dac, Stephanie Myka; Florin, Shyra Marie, Julio, Angel; Simangan, Sidmyr Sosthenes; Soriano, Sophia Theresa; Viadro, Marc Francis; Villanueva, Andrea Amor 4 0 16; 5
ABSTRACT: This study was based on the perceptions of jeepney drivers and commuters in Manila on gas price hikes. It aimed to determine their perceived level of effect of gas hike and their perceptions on the effect of the gas hike in certain factors, mainly: earnings, efficiency, livelihood, daily budget, practically, and accessibility. This study used a quantitative research design which allowed the researchers to use the statistical tools such as: weighted mean, ranking. ANOVA, and simple linear regression to analyze the data gathered. A survey questionnaire was used to gather data from the respondents. These were distributed via online and in-person interactions. The researchers found that the jeepney drivers were extremely affected by the gas hike, while the commuters were very affected by the gas hike, in which, there was a significant difference on their perceived level of effect of gas hike.
Business Research: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2